THE USE OF ARTIFICIAL INTELLIGIENCE IN TEACHING LITERATURE TO ADULT LEARNERS (Journal of Universal Science Research, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed educational practices, including the teaching of literature. This article explores the role of AI in teaching literature to adult learners, focusing on its pedagogical potential, challenges, and implications.